Edukasi Media Tanam Inovatif Dari Bahan Sisa Rumah Tangga - Alam, Megawati Citra; Utomo, Budi; Dewi, Yuni Rosita; Herdajanto, Trijadi; Putra, Dimas Ganda Permana; Baharuddin, Ricko; Syafitri, Sukma Dewi (Universitas Gajah Putih, 2022)
Making Innovative Planting Media from Unused Materials is a community service outreach activity that was carried out immediately with the Faculty of Agriculture at SMP Negeri 3 Gondang. Students are very eager to learn new material and can work on it for extended periods of time in class. With the existence of this activity, a mutualistic symbiosis between the plant faculty and the SMPN 3 Gondang was formed. SMPN 3 Gondang has the potential to be a top-notch school that combines theory and practice to teach Merdeka curriculum, even though the Faculty of Agriculture lacks a dedicated space for teaching Merdeka Belajar Kampus Merdeka (MBKM). This activity will continue to be carried out in the future with different themes.